Outcome of Initial Progression During Nivolumab Treatment for Hepatocellular Carcinoma: Should We Use iRECIST? - Lee, Dong Ho; Hwang, Sangyoun; Koh, Young Hwan; Lee, Kyung-Hun; Kim, Ju Yeon; Kim, Yoon Jun; Yoon, Jung-Hwan; Lee, Jeong-Hoon; Park, Joong-Won (Frontiers in Medicine, 2021)
Immune response evaluation criteria in solid tumors (iRECIST) is recommended during immune checkpoint inhibitors (ICIs) treatment, due to the possibility of pseudoprogression. We evaluated the frequency of pseudoprogression in hepatocellular carcinoma (HCC) patients. This retrospective multicenter study involved 158 consecutive patients who underwent nivolumab treatment for HCC in Korea. At the initial evaluation, 94 patients presented with immune unconfirmed progressive disease, and 22 continued nivolumab. At the second evaluation, 21 of the 22 patients (95.5%) had confirmed progression and no pseudoprogression was observed. Considering low possibility of pseudoprogression, iRECIST may not be required for HCC.